2018
DOI: 10.21037/tau.2018.04.12
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury and male infertility—a review of current literature, knowledge gaps, and future research

Abstract: Spinal cord injury (SCI) affects nearly half a million new patients worldwide, with 17,700 in the US each year, and disproportionately impacts young males of reproductive age. Almost every aspect of male reproduction is affected by SCI, resulting in: erectile, endocrine and sexual dysfunction, decreased sperm motility despite an often-normal count, and abnormal semen emission and ejaculation. The aim of this review is to focus on how SCI impacts testicular spermatogenesis, sperm function, semen quality, and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 75 publications
0
12
0
1
Order By: Relevance
“…So far, low sperm count or poor motility and quality of sperm induced male infertility still affected male (24). Testicular microcirculation induced change of spermatogenesis is a common cause for male infertility [25].…”
Section: Discussionmentioning
confidence: 99%
“…So far, low sperm count or poor motility and quality of sperm induced male infertility still affected male (24). Testicular microcirculation induced change of spermatogenesis is a common cause for male infertility [25].…”
Section: Discussionmentioning
confidence: 99%
“…ED, ejaculatory dysfunction, and semen abnormalities contribute to the problem [ 65 ]. SCI is a highly inflammatory process that affects multiple organs that we do not fully understand, including the testis [ 66 , 67 ]. Moreover, reactive oxygen species (ROS) are higher in SCI men, and there is an inverse correlation between the level of ROS and sperm motility [ 67 , 68 ].…”
Section: H 2 Modulates Sexual Organs Homeostasimentioning
confidence: 99%
“…SCI is a highly inflammatory process that affects multiple organs that we do not fully understand, including the testis [ 66 , 67 ]. Moreover, reactive oxygen species (ROS) are higher in SCI men, and there is an inverse correlation between the level of ROS and sperm motility [ 67 , 68 ]. Ge et al investigated the effects of H 2 -rich saline on the testicular biological function by establishing a hemi-sectioned spinal cord injury (hSCI) rat model (laminectomy at the T10-T12 level); they found that H 2 -rich saline upregulated the reduced ratio of testis weight/body weight, attenuated testicular morphological injury, improved the ultrastructural damage of cells in testis, increased the downregulated mean seminiferous tubular diameter and seminiferous epithelial thickness, reduced apoptosis of spermatogenic cells, increased testicular mitofusin-2 (an outer mitochondrial membrane GTPase involves in mitochondrial fusion and endoplasmic reticulum-mitochondria tethering [ 69 ]), and decreased testicular heme oxygenase-1 (HO-1, an enzyme catalyzes oxidation of heme to biologically active molecules: iron, a gene regulator; biliverdin, an antioxidant; and CO, a heme ligand [ 70 ]) and high-mobility group box 1 (HMGB-1, an endogenous danger signal and inflammatory mediator) levels in rats subjected to hSCI [ 71 ].…”
Section: H 2 Modulates Sexual Organs Homeostasimentioning
confidence: 99%
“…If the damage is significant enough, the ED patient will not respond to PDE5i therapy. Furthermore, spinal cord injury can directly damage nerves, resulting in damage to or the attenuation of sexual activity-related nerve reflex arcs, e.g., nerves and blood vessels in the penis, by altering neuroendocrine reflexes [21,28]. Such traumas involving injury to nerves, blood vessels, and cavernous tissues related to erectile function can cause the abovementioned adverse events.…”
Section: Possible Causes For Ed In Pde5i Nonrespondersmentioning
confidence: 99%
“…As diabetes can disrupt the balance of sex hormones, such as by lowering testosterone levels to affect erection function [ 19 - 20 ], the presence of such comorbidities may be an important cause of PDE5i nonresponsiveness. In addition, the side effects of some drugs used for comorbidities, such as selective serotonin-reuptake inhibitors, thiazides, and β-blockers, affect erectile function and thereby weaken the effect of PDE5is on ED [ 21 - 22 ]. Interestingly, unhealthy behaviors, such as excessive drinking, smoking, and a high-fat diet, can also promote the development and progression of these comorbidities in men, in turn affecting the efficacy of PDE5is in the treatment of ED [ 23 - 25 ].…”
Section: Possible Causes For Ed In Pde5i Nonrespondersmentioning
confidence: 99%